1997
DOI: 10.1016/s0925-4773(97)00057-9
|View full text |Cite
|
Sign up to set email alerts
|

The Evil proto-oncogene is required at midgestation for neural, heart, and paraxial mesenchyme development

Abstract: The ecotropic viral integration site-1 (Evi1) locus was initially identified as a common site of retroviral integration in myeloid tumors of the AKXD-23 recombinant inbred mouse strain. The full-length Evi1 transcript encodes a putative transcription factor, containing ten zinc finger motifs found within two domains of the protein. To determine the biological function of the Evi1 proto-oncogene, the full-length, but not an alternately spliced, transcript was disrupted using targeted mutagenesis in embryonic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
145
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(161 citation statements)
references
References 40 publications
10
145
2
Order By: Relevance
“…These data also suggest that the mechanisms/pathways utilized by EVI1 are not independent of genetically encoded cellular characteristics. These data are in agreement with those of investigators who suggested that EVI1 might have a crucial function in cellular proliferation and differentiation [1] and that might promote the cell proliferation [14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data also suggest that the mechanisms/pathways utilized by EVI1 are not independent of genetically encoded cellular characteristics. These data are in agreement with those of investigators who suggested that EVI1 might have a crucial function in cellular proliferation and differentiation [1] and that might promote the cell proliferation [14].…”
Section: Discussionsupporting
confidence: 93%
“…This paper is based on a presentation at the Seventh International Workshop on Molecular Aspects of Myeloid Stem Cell Development and Leukemia in Annapolis, Maryland, May [13][14][15][16] 2007, sponsored by The Leukemia & Lymphoma Society.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…This is confirmed by recent work showing that the disruption of the full-length Evi1 transcript by targeted mutagenesis of embryonic stem cells results in the death of mutant embryos at approximately 10 5 . 26 Homozygous Evi1-/-embryos were readily identified by hemorrhaging and malformation of the paraxial mesoderm. Histological analysis revealed widespread hypocellularity, defective myotome formation, defects in the neural ectoderm, and failure of the peripheral nervous system to develop.…”
Section: Evi1 Expression and Functionmentioning
confidence: 99%
“…The cellular proliferation defects noted in mutant embryos would support the involvement of Evi1 in dysregulated cell growth observed in retrovirus-induced leukemias. 26 Studies of the function of murine and human EVI1 in bone 2024 marrow cells and in cell lines have shown that the inappropriate expression of EVI1 prohibits terminal differentiation in granulocytes, erythroid cells, and bone marrow progenitor cells. 27,28 Some of these studies utilized the IL-3-dependent murine cell line 32Dc13.…”
Section: Evi1 Expression and Functionmentioning
confidence: 99%
See 1 more Smart Citation